The perspective of rights of the peoples, the intersectional perspective and the integrality of the practices, as axes for degree and postgraduate training in universities (Praxis Educativa, 2020)
This paper aims to contribute to the reflections on the conceptions of human rights from which we intervene in our practice in public universities. The look we propose an anchor in the perspective of peoples' rights and their dialogues with Latin American critical pedagogy. The work investigates the integrality of the practices and emphasizes the curricularization of the university extension from the perspective of peoples' rights. It also raises the need to assume the intersectional perspective in human rights pedagogy.
Keywords: human rights; peoples’ rights; intersectionalities; university extension; - university teaching.